การศึกษาโครงสร้างจุลภาคและค่ามอดุลัสของยังของโลหะผสมไทเทเนียม Ti-AI-V-Nb - อนัญญา รัมมะทรง (จุฬาลงกรณ์มหาวิทยาลัย, 2009)
Nowadays, the titanium alloys are widely used for orthopedic implants because of their excellent properties compared with stainless steels 316L, cobalt base alloys. However, its Young’s modulus is still more than modulus of bone, so it causes a pain in joining area and to loose of implant. This work was intended to develop the Ti6Al4V titanium alloy to have an appropriated Young’s modulus for orthopedic implant. Initially, the Ti6Al4V titanium alloy scrap and pure niobium 2, 6, 8 and 12 weight percent were melted by vacuum arc melting furnace. The effect of niobium content on young’s modulus of titanium alloys were experimented by Grindosonic tester. To support the measured young’s modulus of these alloys, the hardness was tested and microstructure was also observed by optical and scanning electron microscopes. Furthermore, to study corrosion behavior of those alloys, the polarization curves were evaluated in Hank’s balance salt solution at 37 degree Celsius. Based on experimental results, microstructure of the Ti-Al-V-Nb alloys were a typical Widmanstätten structure, acicular alpha on beta matrix. The acicular alpha decreased when niobium content increased which resulted in the effect on young’s modulus of the as-cast titanium alloys. Increasing of the niobium content up to 11.42 weight percent in the as-cast Ti-Al-V-Nb, the young’s modulus decreased from 107 GPa to 89 GPa. Heat treatment of the as-forged those alloys resulted in increasing the young’s modulus up to 8 times. However, the corrosion behavior of all as-cast Ti-Al-V-Nb alloys showed no any significant change by potentiodynamic polarization measurement.